Pendampingan SMK Pusat Keunggulan melalui Penguatan Roadmap Strategis dan Link and Match DUDIKA di Belitung: Mentoring a Vocational High School Center of Excellence Through Strengthening the Strategic Roadmap and Link-and-Match Partnerships with the Business, Industrial, and Workforce Sectors in Belitung - Albar, Berri Brilliant; Amsal, Ares Albirru (LPPM Universitas Andalas, 2026)
This community engagement program aimed to accelerate the institutional transformation of Vocational High School 1 Tanjungpandan, Belitung Regency, as a designated Vocational High School Center of Excellence (SMK-PK). The school faced several institutional challenges, including misalignment between its long-term strategic vision and operational roadmap, limited collaboration with business, industry, and the workforce (DUDIKA), and the absence of standardized Project-Based Learning (PjBL) models. As part of a national initiative entrusted to Universitas Andalas, a structured university-led mentoring program was implemented over a six-month period. The program employed a Participatory Action Research (PAR) approach combined with collaborative workshops involving 35 participants, including the principal, the Center of Excellence (CoE) team, and vocational teachers. The intervention consisted of institutional mapping, site observations, strategic roadmap revision workshops, curriculum alignment, and the development of Teaching Factory (TeFa) frameworks to strengthen school–industry collaboration. The results demonstrated significant institutional progress, including the complete revision of the strategic roadmap in alignment with industry needs, the development of three new Project-Based Learning (PjBL) instructional modules, and the establishment of formal internship partnerships with five local DUDIKA partners. These outcomes strengthened institutional governance, improved curriculum relevance, and enhanced collaboration between the school and industry. Overall, the program demonstrates that systematic university-led mentoring is an effective strategy for supporting vocational school transformation, reducing implementation challenges, and fostering sustainable link-and-match partnerships with industry. This mentoring model offers a practical and replicable framework for strengthening vocational education, particularly in geographically remote and island regions.